FEMINIST LEADERSHIP FOUND ON QUEEN INGRITH IN “ MALEFICENT : MISTRESS OF EVIL”FILM - Meo, Maria Y; Wanggai, Febe F I; Liru, Marianus W (Fakultas Hukum dan Sosial Humaniora Universitas Flores, 2023)
The aims of this study were to find the elements of feminist leadership and how the influence effects of feminist leadership that arise in the development of Queen Ingrith's character in the film